(untitled) (Global Journal of Management and Business Research, 2020)
An increase in the awareness of the various problems that environment is facing has led to a drastic change in the buying patterns of consumers on how do they consume the products. There has been a change in consumer preferences towards environmentally friendly and sustainable products. People are willingly and actively trying to lessen their usage patterns of products, which are detrimental to the environment. However, the concept of green marketing, which came into prominence in the late 80s, still has different interpretations from the customer as well as the marketer’s point of view. Although in Academics, green marketing has a specific meaning, but when it comes to companies Green marketing has a very hazy understanding which needs proper understanding. The present study tries to explore the concept of green marketing qualitatively.